Evaluation of How Nursery Pig Performance is Affected by Fermented Corn Protein as a Replacement to Enzymatically Treated Soybean Meal Along With High or Low Branch Chain Amino Acid to Leucine Ratios - Ethan B. Stas; Jenna A. Chance; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth; Joel M DeRouchey; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
Two experiments were conducted to determine if fermented corn protein can serve as a replacement to enzymatically treated soybean meal and what the effects may be with high or low branch chain amino acids (BCAA):Leu ratios on nursery pig performance. In Exp. 1, a total of 350 barrows (200 × 400, DNA; initially 13.2 lb) were randomly allotted to 1 of 5 treatments with 5 pigs per pen and 14 replications per treatment. Dietary treatments were arranged in a 2 × 2 + 1 factorial with a control diet or diets with 5 or 10% fermented corn protein or enzymatically treated soybean meal. Pigs were fed phase 1 diets for 10 d followed by phase 2 diets for 21 d. There were no interactions observed throughout the experiment. Overall (d 0 to 31), pigs fed increasing levels of fermented corn protein had decreased (linear,P≤ 0.026) BW, ADG, and ADFI with no differences in F/G, whereas increasing enzymatically treated soybean meal had no effect on growth performance. Pigs fed enzymatically treated soybean meal had improved (P≤ 0.034) BW, ADG, and F/G compared to pigs fed fermented corn protein diets, with no effect on ADFI. In Exp. 2, a total of 350 pigs (241 × 600, DNA; initially 26.7 lb) were used to determine the effects of fermented corn protein with high or low BCAA:Leu ratio on nursery pig growth performance. At weaning, pigs were randomly assigned to pens (5 pigs per pen). On d 24 after weaning (d 0 of the trial), pens of pigs were weighed and then allotted to treatment. Pigs were assigned to 1 of 5 dietary treatments with 14 replications per treatment. Dietary treatments were arranged in a 2 × 2 + 1 factorial. Diets consisted of 10 or 20% fermented corn protein either with high or low BCAA:Leu in addition to a control diet. There was no interaction observed between fermented corn protein concentration and BCAA:Leu. Overall (d 0 to 21), BW, ADG, ADFI, and F/G worsened (linear,P<0.001) as fermented corn protein increased in the diet. High BCAA:Leu improved (P= 0.023) F/G compared to low BCAA:Leu with no effect on BW, ADG, and ADFI. In summary, using fermented corn protein to replace enzymatically treated soybean meal in phase 1 and 2 diets of nursery pigs diminished growth performance. Increasing concentrations of fermented corn protein in phase 3 worsened growth performance and increasing BCAA:Leu only improved the feed efficiency.
Keywords: nursery pig; fermented corn protein; enzymatically treated soybean meal; branch chain amino acids